THE STUDY OF MORAL VALUES EDUATION THROUGH THE LIVING VALUES ACTIVITIES PROGRAM TO DEVELOP STUDENTS CHARACTER IN SENIOR HIGH SCHOOL PLUS MUTHAHHARI BANDUNG - Hayati, Auliya (Department of Civic Education, 2015)
SMA Plus Muthahhari come with the Living Values Activities program which is full of living values. The results showed: (1) The moral values education contents through LVA program consists of Personal Development Program,X-Day,Dirasah Islamiyyah; (2) The moral values education method through LVA program consists of using the general method, special method, integrated model; (3) The moral values education process through LVA program covering by the phase of Value Identification, Activity, Learning Aids, Interactions Unit, Segment and Evaluation; (4) The problem of Values Education through LVA Program is a complex moral value measurements, the rules of moral values is not Perfectly executed, the less time; (5) The follow-up moral values education problem through the LVA program: bring students on real life conditions that are different from their daily life, held a sustainable menu system, Improving communication between the parties, and optimizing moral values education quality.The Keyword : Moral Values Education, Living Values Activities, Student Character